PERKEMBANGAN KOGNITIF, FISIK-MOTORIK, SOSIO-EMOSIONAL DAN PENDIDIKAN PAI PADA MASA ANAK - Sulistia, Ulmi; Rokhimawan, Agung; Suryana, Yayan (Wahdatul Ulum Institute, 2023)
Development is a systematic, continuous and progressive process of individual change in accordance with the continuous emergence of new traits from the beginning to the end of life. In general, childhood is divided into two parts, namely early childhood and late childhood. The aim of this research is none other than to find out about cognitive, physical-motor, socio-emotional and educational development during childhood. The results of this research show that cognitive development is the stages of change that occur in the span of human life to understand, manage information, solve problems and know things. Motor development is a term used to describe the movement behavior carried out by the human body. Socioemotional or emotional development in childhood is characterized by the emergence of evaluative emotions which include feelings of pride, shame and guilt, where the emergence of these emotions shows that children have begun to understand and use social rules and norms to assess their behavior.